Financial Performance Analysis and Z-Score Assessment of Pharmaceutical Industry During and After Economic Crisis In 2020 - Habib Muhammad Dwana Nugraha; Raden Aswin Rahadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study discusses the analysis of financial performance and potential bankruptcy of all publicly listed pharmaceutical companies in Indonesia during and after the COVID-19 pandemic. This study uses financial ratio analysis such as Liquidity, Solvency, Profitability, and Activity Ratio as well as bankruptcy potential assessment with the Altman Z-Score Model. This research aims to evaluate the financial conditions of companies and identify the financial risks faced by the pharmaceutical industry in Indonesia. Statistical approach Kolmogorov-Smirnov, Paired T-Test, and Wilcoxon Signed Rank Test, to asses significant change in financial performance during and after pandemic. The results of this study indicate that PT Kimia Farma (KAEF), PT Indonesia Farma (INAF), PT Pharos (PEHA), and PT Pyridam Farma (PYFA) have poor financial conditions based on the results of all poor financial ratios, Moreover, these companies showed significant bankruptcy potential, with Altman Z-Score values below 1.89. and for SOHO it also has a poor profitability ratio especially in Gross Profit Margin categorizing them in the